STUDI KOMPARASI ANTARA PRACETAK MASIF DAN FLY SLAB STUDI KASUS : STRUKTUR GEDUNG RUSUNAWA SURAKARTA - Aria Wirawan; Budi Wicaksono; Nuroji Nuroji; Windu Partono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Fly slab is one of the precast concrete slab technological development that has been researched and patented by Ir . Sulistyana in 2011. The concept is how to reduce the mass of precast concrete slab with makes ribs on the concrete slab. To minimize the volume of concrete plate and while maintaining tensile area to makes the style transfer mechanism of concrete to reinforcement or otherwise, are expected to reduce the mass of the structure without reducing strength.Comparative study will be conducted in the final project based on Planning of Building Construction Rusunawa in Surakarta, Central Java 2013. This comparative study is done by compare the results of the structural design Rusunawa existing Surakarta and ready to build using conventional precast concrete massive, with a new structure plan Rusunawa Surakarta with using fly slab as material plate, beam and column structural elements using conventional concrete.Based on the analysis results, showed reduction in the volume of concrete and reinforcement elements beam and coloumn Rusunawa Surakarta structure is 20,25% and 6,3 %. Reduction reaction in the vertical structure of the Rusunawa Building in Surakarta is 16,93%.